INCIDENTAL DETECTION OF CARCINOMA IN SITU IN FIBROADENOMA OF BREAST IN A YOUNG WOMAN: A RARE FINDING - Valerina Kairanna, Nikitha; Kumar Singh, Brijmohan; P, Pavithra (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Fibroadenoma is the most common benign tumor of the breast in young females. Breast cancer arising within a fibroadenoma is a rare phenomenon. The incidence of carcinoma within a fibroadenoma is reported to be between 0.1% and 0.3% in a screened population, with a peak age of occurrence between the 4th and 5th decade. We present a case of 29-year-old female with ductal carcinoma in situ in a background of fibroadenoma. There is a low percentage of fibroadenomas harboring carcinoma; however, all breast lumps should be seriously managed; extirpation and histological examination is recommended.